The Chronicle of ZVS 2025. The art of intelligences - Sergeev, Alexey; Grigoryeva, Elena; Tkacheva, Marina (project baikal, 2025)
The article describes the events of ZVS-25 and the events on the theme of the festival “Artificial and natural intelligence. Architecture of the future”. The innovative placement of the exposition and its advantages are noted. The article gives an overview of the excursions, a round table, workshops and discussions, and also describes the participants and the winner of the festival, as well as the award ceremony.